COMPLIANCE AND INTERNATIONAL REGULATION: HOW TO ENSURE CONFORMITY WITH INTERNATIONAL LAW AND AVOID LEGAL RISKS - Stradella, Rafaella (Revista Sistemática, 2021)
In today’s interconnected global economy, compliance with international regulations is a critical priority for both public and private entities operating across borders. Adhering to diverse international legal frameworks—ranging from anti-corruption conventions and trade rules to data protection and environmental agreements—poses significant challenges due to legal complexity, extraterritorial enforcement, and cultural diversity. This article examines the multifaceted strategies necessary to achieve effective international compliance, including the internalization of legal norms, risk assessment, and continuous adaptation to evolving regulations. It highlights the importance of proactive governance, cross-border cooperation, and the use of both hard law and soft law instruments. Furthermore, the article addresses how cultural and jurisdictional differences demand contextualized compliance approaches, underscoring that globalization has resulted in hybrid regulatory regimes rather than uniformity. Ultimately, fostering a culture of ongoing legal conformity is essential for mitigating risks and promoting sustainable, ethical business practices in an increasingly complex international landscape.